Citra Destinasi Wisata Religi Berdasarkan Pengalaman Wisata pada Prosesi Semana Santa di Kota Larantuka - Olivia Caterine Dora Maran; Herry Santosa; Jenny Ernawati (Journal on Education, 2022)
Larantuka was once a catholic kingdom with a religious tradition called Semana Santa which lasted hundreds of years. Semana Santa, which now has developed into a religious tourism attraction, is a combination of history and religious rituals which together with the physical environment together form the image of religious tourism in Larantuka City. However, in its development, Larantuka is increasingly experiencing changes, not only socially, but physically, which then affects the identity of the area which is well-known as a religious tourism destination. Through mental mapping carried out on 32 respondents who took part in Semana Santa, a description was obtained in the form of an overview of Larantuka based on the experience of religious tourism as expressed by 58 environmental attributes. The grouping of the 58 environmental attributes is after known as the image-forming elements of religious tourism destinations, namely Tourism Locations-Sacral Sites, Tourist Locations-Non-Sacral Sites, Activity Support Facilities-Sacral Sites, Other Activity Support Facilities, Transportation Facilities, Linear Attributes, Watershed Landscapes, Local Community Organizations/Settlements, Land Views and Shopping. The ranking for the frequency of describing attributes shows that rankings 1 to 10 are dominated by environmental attributes in the category "Tourist Locations-Sacral Sites". This can indicate that the role of sacred environmental attributes still strongly influences the destination image of Larantuka City compared to other environmental attributes.